Conference Report: Clinical and Pharmaceutical Solutions through Analysis (CPSA USA 2013): Connecting Patients and Subject Numbers Through Analysis. (February 2014) - Needham, Shane; Premkumar, Noel; Weng, Naidong; Lee, Mike
The 16th Annual Symposium on Clinical and Pharmaceutical Solutions through Analysis (CPSA) 7–10 October 2013, Sheraton Bucks County Hotel, Langhorne, PA, USA. The 2013 CPSA brought together the various US FDA regulated analytical fields affecting a 'patient' for the first time – bioanalysts supporting IND and NDAs, clinical diagnostic and pathology laboratory personnel, and clinical researchers that provide insights into new biomarkers. Although the regulatory requirements are different for each of the above disciplines, the unique analytical perspectives that affect the patient were shared – and the goal of the 2013 CPSA – 'Connecting Patients and Subject Numbers Through Analysis' was achieved.